Transcatheter aortic valve replacement versus surgical aortic valve replacement in patients with cirrhosis. Issue 5 (23rd December 2015) - Thakkar, Badal; Patel, Aashay; Mohamad, Bashar; Patel, Nileshkumar J.; Bhatt, Parth; Bhimani, Ronak; Patel, Achint; Arora, Shilpkumar; Savani, Chirag; Solanki, Shantanu; Sonani, Rajesh; Patel, Samir; et al.
Abstract : Objectives: To compare the in‐hospital outcomes in cirrhosis patients undergoing transcatheter aortic valve replacement (TAVR) versus those undergoing surgical aortic valve replacement (SAVR). Background: Over the last 10 years, TAVR has emerged as a therapeutic option for treating severe aortic stenosis in high‐risk patients. Cirrhosis patients have a high risk of operative morbidity and mortality while undergoing cardiac surgery. This study's hypothesis was that TAVR is a safer alternative compared to SAVR in cirrhosis patients. Methods: The study population was derived from the National Inpatient Sample (NIS) for the years 2011–2012 using ICD‐9‐CM procedure codes 35.21 and 35.22 for SAVR, and 35.05 and 35.06 for TAVR. Patients <50 years of age and those who concomitantly underwent other valvular procedures were excluded. ICD‐9‐CM diagnosis codes were used to identify patients with liver cirrhosis, portal hypertension, and esophageal varices. Using propensity score matching, two matched cohorts were derived in which the outcomes were compared using appropriate statistical tests. Results: There were 30 patients in the SAVR and TAVR group each. Compared to the TAVR group, the patients in SAVR group had significantly higher rate of transfusion of whole blood or blood products ( p  = 0.037), longer mean postprocedural length of stay ( p  = 0.006), and nonsignificantly higher mean cost of hospitalization ( p  = 0.2), any complications rate ( p  = 0.09), and liver complications rate ( p  = 0.4). In‐hospital mortality rate was same in the both the groups. No patients in the TAVR group required open‐heart surgery or cardiopulmonary bypass. Conclusion: TAVR could be a viable option for aortic valve replacement in cirrhosis patients. © 2015 Wiley Periodicals, Inc.